Penegakan Hukum Perlindungan Izin Usaha dalam Media Elektronik terhadap Pelanggaran Pidana Perizinan di Indonesia - Khoyron Nasir, Tomi; Prasetyo, Handoyo (CV. Era Digital Nusantara, 2024)
In order to maintain a healthy investment climate competition, the Indonesian Government issued its legal product in the form of Government Regulation Number 24 of 2018 concerning Electronic Integrated Business Licensing Services aimed at enforcing business establishment permits and increasing the increase in the business licensing acceleration index in Indonesia. This article research is a normative legal research. The research aperaturan pemerintahroach method uses the legislative aperaturan pemerintahroach and case aperaturan pemerintahroach to examine the legal problems of the business license. The data source for writing this article comes from a literature study whose sources come from books, papers, and journals related to business licensing law in Indonesia. In writing this article, the author discusses how the legal regulation of licensing law and its solution are related to criminal acts related to violations of business licensing in electronic media in Indonesia nation. The results of this study explain that business activities whose operations in electronic media do not follow the legal regulations of business licensing in Indonesia, then the company can be sanctioned, its license revoked and cannot function properly and comprehensively in its operations in the territory of Indonesia.